A PARADIGM SHIFT IN THE INTERPRETATION OF RELIGIOUS MODERATION IN INDONESIA: A Review of Some Indonesian Mufassir (Al-Wasatiyah: Journal of Religious Moderation, 2023)
Diverse concepts concerning the attitude of religious moderation in Indonesia, which continues to develop, demonstrate how Indonesian Muslim intellectuals view tolerant attitudes toward followers of other religions. There are also Hamka, Bisri Mustafa, and Quraish Shihab, each with their own Tafsir works. The fact that these interpretation figures were born in various generations places them in different circumstances. Using Kuhn's approach to the concept of a paradigm shift (paradigm shift), this article attempts to determine how these figures respond to religious tolerance in Indonesia in their respective works of interpretation by analyzing the shift in interpretation. The analysis will be guided by evaluating an ideology's ideological background, power relations (authority), and fanaticism. This study centers on the verses of religious moderation, specifically surah al-Baqarah [2]: 256, Ali 'Imran [3]: 85, and Al-Kafirun [109]: 1-6, which will also be examined by analyzing sociocultural aspects and interpretation authority. The findings of this study indicate a shift from Madhabi theology to Humanist theology among the figures mentioned above. Bisri Mustafa and Quraish Shihab are more tolerant of differences than Hamka, whose interpretation tends to be more traditional when examining religious and cultural ties. This case demonstrates the influence of diverse Indonesian contexts on the interpretation.